2015
DOI: 10.3390/fi7040484
|View full text |Cite
|
Sign up to set email alerts
|

Improving Teacher Effectiveness: Designing Better Assessment Tools in Learning Management Systems

Abstract: Current-generation assessment tools used in K-12 and post-secondary education are limited in the type of questions they support; this limitation makes it difficult for instructors to navigate their assessment engines. Furthermore, the question types tend to score low on Bloom's Taxonomy. Dedicated learning management systems (LMS) such as Blackboard, Moodle and Canvas are somewhat better than informal tools as they offer more question types and some randomization. Still, question types in all the major LMS ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The articles in this review covering Jan 2015–June 2021 show that most reported advancements in new software developments for Moodle relate to improving assessment processes. The development advancements include improving the security of the assessment processes (Adesemowo et al, 2016 ; Kaya & Özel, 2015 ), improving the mechanisms to generate quiz questions, and improving feedback and response time (Conejo et al, 2016 ; Kruger et al, 2015 ). Security improvements include, but are not limited to, improving user data verification (Amoako & Osunmakinde, 2020 ), facial recognition (Guillén-Gámez & García-Magariño, 2015 ), limiting IP range (Adesemowo et al, 2016 ), and scanning students IDs (Ross, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles in this review covering Jan 2015–June 2021 show that most reported advancements in new software developments for Moodle relate to improving assessment processes. The development advancements include improving the security of the assessment processes (Adesemowo et al, 2016 ; Kaya & Özel, 2015 ), improving the mechanisms to generate quiz questions, and improving feedback and response time (Conejo et al, 2016 ; Kruger et al, 2015 ). Security improvements include, but are not limited to, improving user data verification (Amoako & Osunmakinde, 2020 ), facial recognition (Guillén-Gámez & García-Magariño, 2015 ), limiting IP range (Adesemowo et al, 2016 ), and scanning students IDs (Ross, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Moodle statistics for 2019 show that the most popular plug-ins (based on the number of downloads) were communication and content plug-ins, such as Moove, BigBlueBN, Adaptable, H5P, and Eguru (Moodle Project, 2020b). The articles in this review covering Jan 2015-June 2021 show that most Gamage et al International Journal of STEM Education (2022) The development advancements include improving the security of the assessment processes (Adesemowo et al, 2016;Kaya & Özel, 2015), improving the mechanisms to generate quiz questions, and improving feedback and response time (Conejo et al, 2016;Kruger et al, 2015). Security improvements include, but are not limited to, improving user data verification (Amoako & Osunmakinde, 2020), facial recognition (Guillén-Gámez & García-Magariño, 2015), limiting IP range (Adesemowo et al, 2016), and scanning students IDs (Ross, 2017).…”
Section: Software Development and Adaptationmentioning
confidence: 99%
“…Kemajuan pengembangan termasuk meningkatkan keamanan proses penilaian [12][13], meningkatkan mekanisme untuk menghasilkan pertanyaan kuis, dan meningkatkan umpan balik dan waktu respons [14] [15]. Peningkatan keamanan termasuk, namun tidak terbatas pada, meningkatkan verifikasi data pengguna [16], pengenalan wajah [17], membatasi jangkauan IP [12], dan memindai ID siswa [18].…”
Section: Pendahuluanunclassified
“…Different types of CAA tools have already been developed (Contreras-Higuera et al, 2016;Christie et al, 2015). Many CAA systems and tools allow questions to be generated randomly (Kruger et al, 2015). Piaw argued that replacing paper-based testing with computer-based testing does not cause significant differences in test scores (Piaw, 2012).…”
Section: Introductionmentioning
confidence: 99%